2023
DOI: 10.1122/8.0000558
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of flow curve and categorization of thixotropic yield stress materials

Abstract: Thixotropy is a phenomenon related to time dependent change in viscosity in the presence or absence of flow. The yield stress, on the other hand, represents the minimum value of stress above which steady flow can be sustained. In addition, the yield stress of a material may also change as a function of time. Both these characteristic features in a material strongly influence the steady state flow curve of the same. This study aims to understand the interrelation between thixotropy, yield stress, and their rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 97 publications
1
14
0
Order By: Relevance
“…It is also important to note that soft glassy materials, like bentonite dispersions, may potentially exhibit transient or steady-state shear banding at low shear rates due to rheological aging or inherent nonmonotonic flow curves. 23,[51][52][53][54] These phenomena may not be apparent from traditional bulk rheometry techniques, consequently when reporting the precise values of the yield stress for practical applications, caution must be exercised due to the possibility of shear banding. Corresponding fits were also performed for the decreasing-rate sweeps (and are shown in the ESI, † for clarity).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that soft glassy materials, like bentonite dispersions, may potentially exhibit transient or steady-state shear banding at low shear rates due to rheological aging or inherent nonmonotonic flow curves. 23,[51][52][53][54] These phenomena may not be apparent from traditional bulk rheometry techniques, consequently when reporting the precise values of the yield stress for practical applications, caution must be exercised due to the possibility of shear banding. Corresponding fits were also performed for the decreasing-rate sweeps (and are shown in the ESI, † for clarity).…”
Section: Resultsmentioning
confidence: 99%
“…10 More complex effects such as transient shear banding may also develop in the material. 23 In the intermediate regime between s c 1 and s c 2 , more complicated elastoviscoplastic (EVP) transients are observed, representing the complex interplay between structural break down due to both the accumulated strain, the stress-activated rate of microstructural breakdown and the structural build-up with time. Initially, the young sample is at its most disordered, and therefore continues to build up internal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yield stress depends on the extent of network formation and hydrodynamic interactions between large and small aggregates. Although the phenomenology of yield stress has been replicated using nonlinear viscoelastic constitutive relationships, 46,49,60 it is difficult to directly associate the parameters with the fractal structure of the agglomerates. Following Shih et al 61 model for effective elastic modulus G, and elastic strain γ e , in the strong link regime, the yield stress can be described as…”
Section: Yield Stressmentioning
confidence: 99%
“…44,45 Several new models that respect these thermodynamic considerations have been proposed, typically involving a reformulation of the existing phenomenological models in terms of internal variables such as stresses (or conformation tensor) and plastic component of strain rate. 21,22,25,46 Alternatively, some approaches also derive constitutive models using non-equilibrium thermodynamic formalisms. [47][48][49] Using the single-generator bracket formalism of non-equilibrium thermodynamics (SGBF-NET), Jariwala et al 49 showed that the energy of mixing associated with the particle size distribution is fundamental to generate aggregation and breakage dynamics required to model thixotropic behavior.…”
mentioning
confidence: 99%